Principles and problems in Philippine foreign relations - Baldoria, Pedro L. (Quezon City University of the Philippines, 1956)
"This is an attempt to present the principles and problems of Philippine foreign relations. The materials in this study are the result of careful selection of documents. Articles published in international magazines were added because of their pertinence in the study of Philippine foreign relations. By permission of individual authors, other articles were included, notable those of Dr. Honest A. Villanueva of the Department of History and Dr. Edward Mill of the Department of Political Science"--Preface.
Part I. Geography of foreign policy -- Part II. Philippine-American relations -- Part III. Partners in democracy -- Part IV. Economic relations -- Part V. Recognition of Philippine sovereignty -- Part VI. Philippine strategy in international politics -- Security in the Pacific -- Part VII. Development of the good neighbor policy -- International understanding -- Regional security -- Part IX. Foreign policy of the Philippines -- Philippines and the United States.
Keywords: Philippines -- Foreign relations